Modeling of microstructure evolution during cold wire drawing process and properties determination - Rengarajan Karthic Narayanan (2012)
Wire drawing is the most widely employed process for manufacturing the micrometer sized gold wire (φ10 − φ50 μm) used for electronic interconnects. Currently, gold wire is applied in the bonding pad and miniaturization has resulted in need of higher quality of wire; wire quality is dependent on mechanical properties. The mechanical properties are based on microstructural behavior. This thesis deals with constitutive modeling and development of a computational framework for the simulation of micromechanical and microstructural behavior of polycrystalline face centered cubic metal such as copper and gold. This is applied to simulate the cold wire drawing and wire bonding processes. Of particular interest are two important phenomena: texture evolution and bond pad cratering. To model the constitutive behavior, a rate independent crystal plasticity with finite strain is implemented as a user routine in commercial finite element (FE) package ABAQUS. An enhanced algorithm has been implemented that takes into account active crystallographic slip and orientation effects to improve the quality of predicted textures. This framework is used to study the micromechanical behavior of copper wire when subjected to drawing and bond pad cratering. Initially, cold drawing process is simulated according to industrial process conditions based on a J2 plasticity theory. The material under consideration is gold wire. The residual stresses on the transverse cross section of the cold drawn gold wire is studied to analyse the strain inhomogeneity which gives an approximate measure of the anisotropic properties in the wire. Micro indentation simulations are then conducted on the drawn wire at different positions across the transverse cross section to understand the mechanical response due to cold work. The defor-mation characteristics of the wire are thus studied in detail using this finite model. The simulation results are compared with those from experiments to ascertain the trend of strain localization. This paved the way for modeling the microstructural and micromechanical behavior using a crystal plasticity finite element frame work. Due to the rising cost of gold wire and considering the volume used in wire bonding industry, attention has turned towards low cost copper as an alternative. The mechanical and electrical properties of copper are found to be superior compared to gold, which is also a major factor in this change. The wire drawing of copper using the rate independent crystal plasticity finite element (CPFE) is thus also of interest in this thesis. The anisotropy of the copper single crystals with respect to crystallographic orientations are understood using nanoindentation finite element simulations. Then, the texture evolution of the drawn polycrystalline copper wire is studied in detail. The experimental texture evolution of the wire after drawing is compared with the simulated results. The enhanced model in this work is shown to improve texture predictions. An additional point of interest is the application of crystal plasticity finite element model on the bond pad cratering. During the wire bonding process, the free air ball impacts on the soft aluminum metallization pad leading to squeeze out from the pad. The effect of copper free air ball texture during this impact stage on the bond pad is also analysed and explained. The failure of the aluminum pad affects the reliability of the process.